(3HjGf aVd NjGQ GdfGS hGdcTa Yf ecQ GdhShGSs - (3Ydj Hf ejehf Hf CHj HcQ Hf jhSa GdgGTej GdMSfj GdEOQjSj GdaGSj GdeZQHj, GHf ejehf , CHh GdMSf,J (B917 (3g` s ((3YHO GdhgGH Hf SdjeGf GdghT s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CeG HYO CjgG GdeJbQH Edi HUdGJg hUheg GdeaQhVjf hSfJg hfbdg GdeMahXjf Ke EYde Cf COfi OQLGJ GdENdGU Cf JCJi HYHGOJc SGdeI ef GdNhGWQ cdgG s
(3BNQgG (B:s
(3hQKhg Yf QShd Udi Gddg Ydjg hSde hZjQ gPG dGjLhR ai Mbge aEf TQage HTQa eJHhYge hGddg JYGdi jhabfG hEjGce dUGdM Gdbhd hGdaYd hgh MSHfG hfYe Gdhcjd hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B741s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs